Compassion Fatigue Among the Intimate Partner Violence and Sexual Assault Workforce: Enhancing Organizational Practice - Voth Schrag, Rachel J. (Violence against women, 2022)
Gaps in knowledge related to occupational stress among the intimate partner violence (IPV) and sexual assault (SA) workforce remain. This study examined associations between key risk factors for occupational stress and compassion fatigue among a sample of IPV/SA service providers in the Southwestern United States (N = 520). Results of the hierarchical regression analysis identified microaggressions, age, recent life stress, direct practice, and workload as factors associated with compassion fatigue. The findings point to the importance of incorporating trauma-informed organizational approaches to address microaggressions, reduce workload, and support staff experiencing recent stress and providing direct services.